Extreme integral polynomials on a complex Banach space - Dineen, Seán (MATHEMATICA SCANDINAVICA, 2003)
We obtain upper and lower set-theoretic inclusion estimates for the set of extreme points of the unit balls of $\mathcal{P}_{I}({}^{n}\!E)$ and $\mathcal{P}_{N}({}^{n}\!E)$, the spaces of $n$-homogeneous integral and nuclear polynomials, respectively, on a complex Banach space $E$. For certain collections of Banach spaces we fully characterise these extreme points. Our results show a difference between the real and complex space cases.